Bimodal annual reproductive pattern in laboratory-reared marbled crayfish - Vogt, Günter (Invertebrate reproduction & development, 2015)
The marbled crayfish, Procambarus fallax f. virginalis, is a new research model and potent invader of aquatic ecosystems that reproduces by obligatory parthenogenesis. My data show that in captivity, it can reproduce throughout the year. However, when kept at constant 20 °C and natural photoperiod there were two prominent spawning maxima, one before the spring equinox and another one before the fall equinox. If temperature fluctuated between 15 °C in winter and 25 °C in summer, the first maximum was shifted beyond the spring equinox and the second maximum was shifted closer towards the fall equinox. These results indicate a bimodal annual rhythm for the reproduction in marbled crayfish that can be modulated by temperature. Comparison with P. fallax suggests that this rhythmicity was inherited from its sexually reproducing mother species. Potential consequences of my laboratory findings for wild populations of marbled crayfish in temperate and tropical regions are discussed. Since marbled crayfish can be kept in captivity for up to four years under a broad range of conditions, they offer the possibility to investigate endogenous circannual rhythms and their entrainment by environmental zeitgebers in decapod crustaceans.
Gesehen am 25.06.2020